Aerogels from CdSe/CdS Nanorods with Ultra‐long Exciton Lifetimes and High Fluorescence Quantum Yields. (1st September 2015) - Sánchez‐Paradinas, Sara; Dorfs, Dirk; Friebe, Sebastian; Freytag, Axel; Wolf, Andreas; Bigall, Nadja C.
<x xml:space="preserve">Abstract</x> Hydrogels are fabricated from CdSe/CdS seeded nanorod building blocks by the addition of hydrogen peroxide and converted to aerogels by supercritical drying. The aerogels show higher photoluminescence quantum yields and longer lifetimes than the hydrogels and the nanoparticle solutions. A model for this observation is derived.